PERILAKU HEDONISME MAHASISWA DI TRANS STUDIO - Adinda Azzarah, Pramesty Nurul (Universitas Islam Negeri Alauddin Makassar, 2019)
This research was conducted to see how the behavior of student hedonism in the Trans Studio Mall Makassar. There are several objectives in this paper, namely to analyze the factors that influence the behavior of student hedonism in Trans Studio Mall Makassar, 2) To analyze the forms of student hedonism behavior in Trans Studio Mall Makassar, 3) To find out the impact caused by the behavior of student hedonism in Trans Makassar Studio Studio. There is also the type of research used is a type of qualitative research, with a sociological approach using the logic and theories of sociology both classical and modern theories. Data collection methods used are observation, interviews, and documentation. Data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation, and drawing conclusions.The results of this study indicate that: 1) Factors that influence the behavior of hedonism in students are divided into two, namely internal factors and external factors. Internal factors are happy with the crowd, hobby shopping and want to enjoy youth. External factors are factors that originate from the family environment and social environment, such as parents who accustom their children to luxurious living since childhood, peers, social environment, social media. 2) The forms of student hedonism behavior shown by students in Makassar's Trans Studio Mall are shopping and hanging out in a café. 3) The impact arising from the behavior of student hedonism in the Trans Studio Mall Makassar is divided into two, namely positive and negative impacts.